Analysis of value creation in a leveraged buyout (LBO) operation in Brazil - Mitre Filho, Marcelo; Albuquerque, Andrei Aparecido de; Paixão, Michel Augusto Santana da (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
Using a business model based on the acquisition of companies with growth potential, private equity funds have developed acquisition tools that optimize the value of investments for their shareholders through leveraged buyouts (LBOs). This paper aims to verify if there was value creation or destruction in an LBO operation in the Brazilian market. To study this issue, a business acquisition operation using LBO was observed. The completed operation—from acquisition to divestment—occurred between 2009 and 2013. Economic Value Added (EVA®) was used as the value creation measure. The findings provided inconclusive evidence regarding the destruction of value in a national LBO operation, indicating that other elements may be responsible for the negative EVA® indicator.